2009
DOI: 10.1167/iovs.08-2534
|View full text |Cite
|
Sign up to set email alerts
|

Role of Formation of an ERK-FAK-Paxillin Complex in Migration of Human Corneal Epithelial Cells during Wound Closure In Vitro

Abstract: ERK regulates cell migration during wound healing in vitro by modulating the phosphorylation of FAK and paxillin and the consequent formation of focal adhesions. An ERK-FAK-paxillin signaling pathway may play an important role in corneal epithelial wound healing in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 27 publications
3
51
0
1
Order By: Relevance
“…5), followed by a second broader activation peak 3-5 hours later. Previous wound healing experiments involved activated ERK in regulating cell migration: Matsubayashi and co-workers demonstrated that inhibition of ERK activation results in markedly reduced movement of the epithelial sheet in wound healing experiments [23] and in corneal endothelial cells ERK has also been shown to affect migration speed [40,41]. Our results confirm the overall ERK involvement in regulating migration speed, and highlight its unique role in determining directional migration.…”
Section: Discussionsupporting
confidence: 83%
“…5), followed by a second broader activation peak 3-5 hours later. Previous wound healing experiments involved activated ERK in regulating cell migration: Matsubayashi and co-workers demonstrated that inhibition of ERK activation results in markedly reduced movement of the epithelial sheet in wound healing experiments [23] and in corneal endothelial cells ERK has also been shown to affect migration speed [40,41]. Our results confirm the overall ERK involvement in regulating migration speed, and highlight its unique role in determining directional migration.…”
Section: Discussionsupporting
confidence: 83%
“…Paxillin was originally identified as a major substrate for the v-Src tyrosine kinase (14), and c-Src and FAK have been identified as key kinases responsible for paxillin tyrosine phosphorylation in response to a variety of stimuli (1,5,24,27,37,47). Although LPS stimulated c-Src and FAK phosphorylation, knockdown of Src with siRNA or overexpression FRANK, a dominant-negative form of FAK, did not block LPS-induced tyrosine phosphorylation of paxillin in HLMVECs.…”
Section: Discussionmentioning
confidence: 98%
“…As described in the Introduction, activation of the ERK signaling pathway requires the participation and mediation of PXN in prostate cancer and non-small cell lung cancer (10,17 (11). Several studies have demonstrated that Erk always gives a positive feedback on PXN and plays an important part in the activitation of PXN and interaction between FAK and PXN (11,22,23). Based on these facts, we decided to examine the expression of p-Erk during this experiment.…”
Section: Discussionmentioning
confidence: 99%